Perancangan dan Implementasi Website Company Profile untuk Villa Harimau di Central Group menggunakan Framework Flask - Tony Tan; Sri Indriyani Ningrum; Tony Wibowo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
Villa Harimau is an exclusive property owned by Central Group Batam, requiring a digital platform to support internal promotional activities and marketing communication. This internship project aimed to design and implement a company profile website for Villa Harimau using the Flask framework, with a layout and design aligned with the brand’s identity and the company’s internal needs. The development process involved observation, interviews, and direct source code editing using Flask, Jinja2, and Bootstrap. The website was built with a modular structure to allow future enhancements, focusing on consistent visuals and efficient navigation. The final result demonstrates a well-organized and visually appealing system that effectively delivers property information to support the company’s internal marketing strategy.